N-Dopant-Mediated Growth of Metal Oxide Nanoparticles on Carbon Nanotubes - Jin Ah Lee; Won Jun Lee; Joonwon Lim; Sang Ouk Kim (Nanomaterials, 2021)
Metal oxide nanoparticles supported on heteroatom-doped graphitic surfaces have been pursued for several decades for a wide spectrum of applications. Despite extensive research on functional metal oxide nanoparticle/doped carbon nanomaterial hybrids, the role of the heteroatom dopant in the hybridization process of doped carbon nanomaterials has been overlooked. Here, the direct growth of MnOx and RuOx nanoparticles in nitrogen (N)-doped sites of carbon nanotubes (NCNTs) is presented. The quaternary nitrogen (NQ) sites of CNTs actively participate in the nucleation and growth of the metal nanoparticles. The evenly distributed NQ nucleation sites mediate the generation of uniformly dispersed <10 nm diameter MnOx and RuOx nanoparticles, directly decorated on NCNT surfaces. The electrochemical performance of the resultant hybridized materials was evaluated using cyclic voltammetry. This novel hybridization method using the dopant-mediated nucleation and growth of metal oxides suggests ways that heteroatom dopants can be utilized to optimize the structure, interface and corresponding properties of graphitic carbon-based hybrid materials.